"It has very good intentions but it's not quite there yet": Graduates' feedback of experiential learning in an MPharm programme Part 2 (TELL Project). (September 2020) - Jacob, Sabrina Anne; Boyter, Anne C.
Highlights: Pharmacy students mainly undertake placements in community and hospital settings. Preference for block placements to allow better integration with staff and site. Majority wanted exposure to non-traditional pharmacy sites such as primary care. Quality assurance vital to ensure tutors and sites provide optimum experience. Possible value in adopting peer-teaching model. Abstract: There is a paucity of studies assessing graduates' perceptions of experiential learning and its effectiveness in preparing them for practice. This information would be important in informing changes to the experiential learning component of pharmacy education. We present Part 2 of a mixed-methods study involving graduates to obtain feedback on their experiential learning experience. Online survey responses and qualitative interviews provided suggestions on improving the experiential learning, which included adopting block placements which would allow for a better placement experience. Having a pre-registration trainee present was beneficial, highlighting the possible value of adopting a tiered-teaching model. Given the poor experience at certain placement sites, quality assurance measures should be adopted to ensure tutors and sites are suited and able to train students for the real-world. The majority wanted feedback from tutors, and indeed this should be formalised as it is a key component in the experiential learning cycle.